Evaluation of prognostic factors in patients with Bell's palsy - Dilli Ram Kafle (Wiley, 2021)
Abstract Background Bell's palsy is a common neurological problem that leads to peripheral palsy of the facial nerve. Most patients have a favorable response with or without treatment while some are left with significant facial deformity. Identification of factors which influence the outcome in patients with Bell's palsy may help clinicians counsel better. Methods A prospective cross‐sectional study was carried out in the Department of Neurology Nobel Medical College, Biratnagar, between February 2020 and February 2021 after obtaining ethical clearance from the institutional review committee. Patients were assessed at the time of presentation to hospital and followed up at 1 week, 1 month, and 3 months after the onset of illness to evaluate for recovery. Results Sixty‐two (61.4%) of 101 patients had a favorable outcome at the follow up on the third month, achieving H‐B grade 2 or lower, while 33 (32.7%) had moderate dysfunction and 6 (5.9%) had severe dysfunction. The following factors were associated with favorable outcome: younger age of onset (p < .001), lower initial H‐B grade of III or IV (p = .001), lesser degree of amplitude reduction on affected side as compared to unaffected side (p = .001) and absence of hypertension and diabetes. The following factors did not influence outcome at three months: duration of Bell's palsy (p = 0.142), side of face affected, and gender (p = .09). Conclusions Most of the patients with Bell's palsy have favorable outcomes. Age, hypertension, initial H‐B grade, and extent of facial nerve degeneration as recorded by nerve conduction studies are important predictors of outcome.